SPARC Promotes Aerobic Glycolysis and 5‐Fluorouracil Resistance in Colorectal Cancer Through the STAT3/HK2 Axis - Jingrong Xiang; Huan Zhang; Kanger Shen; Jie Feng; Kexi Yang; Tongguo Shi; Qinhua Xi (Cancer Medicine)
ABSTRACT Background Chemotherapy has been used extensively in the clinic to treat colorectal cancer (CRC). Nevertheless, cancer cells usually develop chemoresistance under chemotherapy stress, leading to treatment failure. At present, the mechanism of chemoresistance in patients with CRC is not fully understood. Methods Firstly, Secreted protein acidic and rich in cysteine (SPARC) expression and prognosis in CRC clinical samples were investigated using tissue microarray (TMAs) and GEPIA databases. Subsequently in vitro, SPARC knockdown or overexpression was used to explore the role of SPARC in 5‐fluorouracil (5‐FU) resistance in CRC cell lines. Western blot or RT‐qPCR was used to analyze the downstream molecules and pathways regulated by SPARC. The contents of glucose and lactic acid were determined by Elisa. In vivo a xenograft tumor model was constructed to verify the function of SPARC in 5‐FU chemoresistance. Results This study revealed a correlation between 5‐FU resistance in CRC and the expression of SPARC. The elevated SPARC expression in CRC tissues was linked to a poor prognosis for CRC patients. SPARC knockdown in CRC cells significantly suppressed aerobic glycolysis and 5‐FU resistance, whereas SPARC overexpression had cancer‐promoting effects. Additionally, SPARC increased 5‐FU resistance through the Signal transducer and activator of transcription 3 (STAT3)/Hexokinase‐2 (HK2) pathway. The impact of SPARC on 5‐FU resistance was eliminated both in vitro and in vivo by blocking HK2 or STAT3 signaling. Conclusion Our results confirmed that SPARC affects the chemoresistance of CRC to 5‐FU through the STAT3/HK2 axis and is one of the indispensable factors affecting the development of 5‐FU resistance in CRC.